2014
DOI: 10.1007/s10517-014-2403-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Patterns of Search and Creative Behavior in Patients with Psychoactive Substance-Induced Disorders

Abstract: The correlation between search and creative behavior with parameters of bioelectric brain activity was observed in patients with addictive disorders. The prevalence of α- and θ-activities in the parietal-temporal-occipital areas of the cortex and increased θ-activity in the right hemisphere in addiction patients with high search and creative activities were associated with enhanced high-frequency activity in these brain areas. These changes can reflect the formation of a focus of pathologically increased excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…At onset of dependence EEG alterations of frequency ranges of bioelectrical activity of the brain occur . In animal studies and clinical studies, it was shown that changes of the level of dopamine involved in pathogenesis of addictive disorders are accompanied by shifts of EEG parameters .…”
Section: Introductionmentioning
confidence: 99%
“…At onset of dependence EEG alterations of frequency ranges of bioelectrical activity of the brain occur . In animal studies and clinical studies, it was shown that changes of the level of dopamine involved in pathogenesis of addictive disorders are accompanied by shifts of EEG parameters .…”
Section: Introductionmentioning
confidence: 99%